PERAN STRATEGIS DAN TANGGUNGJAWAB BKAG DALAM MEMBANGUN RELASI LINTAS IMAN DI KOTA GUNUNGSITOLI - 1Yatri Iman Riani Zebua, 2Hanna Aritonang, 3Adiani Hulu (Universitas Asahan, 2022)
ABSTRACT This research is a qualitativ research. The research subject is BKAG Gunungsitoli city. Data collection methods used are observation and interviews (interviews). This study aims to provide concrete suggestions regarding how to maintain harmony and unity in the pluralistic society of Gunungsitoli city. The results show: the strategic role and responsibility of the Inter-Church Cooperation Agency (BKAG) which does not only focus on the church institution itself regarding dogma, rules and legality. BKAG, which so far only has programs within the church itself, such as Easter and Christmas celebrations between several church denominations that have joined as members. However, through this journal the author hopes that there is a program beyond that, namely participating in maintaining the unity and integrity of the pluralistic Gunungsitoli city community in preventing fanaticism, radicalism, divisions and attitudes that divide religion because the church has a strategic position in conveying and forward the message to the public. The church must be able to have an impact and be a blessing to the nation. Keywords: church, strategic, community, unity, responsibility.